Expert System Toxoplasma Gondii To Detect Disease In Women With Web Based Methods Chaining Forward: Expert System Toxoplasma Gondii To Detect Disease In Women With Web Based Methods Chaining Forward - Gabbi Rinzani; Iskandar Fitri; Nur Hayati (Jurnal Mantik, 2020)
Cases of Toxoplasmosis in humans in Indonesia ranged from 43 to 88%, while in animals ranged from 6 to 70% depending on the type of animal and its region. Many people do not know about this disease because of lack of knowledge possessed. Based on these problems, in this study the expert system uses a web-based forward chaining method to find out information on disease symptoms and to detect early Toxoplasma Gondii in women, so as to reduce the risk of being infected with the Toxoplasma Gondii parasite. This system produces the output that the knowledge material used is based on expert knowledge. In addition, the accuracy of the results of testing this system gets a percentage of 100%.